2023
DOI: 10.1007/s44154-023-00085-2
|View full text |Cite
|
Sign up to set email alerts
|

Global dispersal and adaptive evolution of domestic cattle: a genomic perspective

Abstract: Domestic cattle have spread across the globe and inhabit variable and unpredictable environments. They have been exposed to a plethora of selective pressures and have adapted to a variety of local ecological and management conditions, including UV exposure, diseases, and stall-feeding systems. These selective pressures have resulted in unique and important phenotypic and genetic differences among modern cattle breeds/populations. Ongoing efforts to sequence the genomes of local and commercial cattle breeds/pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Through long‐term adaptation to diverse environments, local breeds have developed unique adaptive traits that enhance their resilience to challenging conditions (Cao et al., 2021; Li et al., 2023; Xia, Qu, et al., 2023). Our study compared Anxi cattle with other breeds to identify specific genomic signatures of selection unique to the Anxi breed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through long‐term adaptation to diverse environments, local breeds have developed unique adaptive traits that enhance their resilience to challenging conditions (Cao et al., 2021; Li et al., 2023; Xia, Qu, et al., 2023). Our study compared Anxi cattle with other breeds to identify specific genomic signatures of selection unique to the Anxi breed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the substantial contributions of cattle, they were rapidly disseminated to various parts of the globe in tandem with human migratory patterns and trade routes. Previous studies have shown that indigenous cattle have distinct local characteristics and can adapt to diverse environments, including hot, cold, and humid climates and highaltitude regions (Chen et al, 2023;Kim et al, 2020;Xia, Qu, et al, 2023;Xia, Zhang, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This variability can lead to differences in fat deposition and meat quality traits among individual animals (Ladeira et al., 2016b). Breed differences in cattle lead to differences in transcriptional profiles that affect the animals' physiological responses, productivity attributes and environmental adaptability (Naskar et al., 2012; Terry et al., 2020; Xia et al., 2023). Genetic diversity and selection forces drive transcriptional changes in many cattle breeds.…”
Section: Transcriptomic Profiling Of Adipose Tissuesmentioning
confidence: 99%
“…Genetic diversity and selection forces drive transcriptional changes in many cattle breeds. Because each bovine breed has a unique transcriptional profile, different cattle breeds exhibit variances in growth rates and muscle development (Tian et al., 2023; Xia et al., 2023). For instance, compared to slower‐growing breeds, breeds bred for rapid growth rates, like the Limousin, have differential expression of genes related to muscle development and hypertrophy.…”
Section: Transcriptomic Profiling Of Adipose Tissuesmentioning
confidence: 99%
“…Indeed, this close host-pathogen relationship of B. abortus with cattle and its high prevalence in unmanaged herds suggests that the evolutionary history of B. abortus may provide unique insights into the history of cattle movements. Then by comparing these genetic patterns in B. abortus to cattle genetics, breeding practices, and livestock movements ( Pitt et al, 2019 ; Verdugo et al, 2019 ; Xia et al, 2023 ), we can understand how socioeconomic forces and cultural practices have spread this pathogen.…”
Section: Introductionmentioning
confidence: 99%